Finansowe mierniki oceny strategii marketingowych przedsiębiorstw - Grzegorczyk, Wojciech (Financial Conditions and Measures of the Marketing Strategies of the Enterprises, 2007)
Between marketing strategy and financial strategy there are mutual interdependencies. It is especially visible when the measurement of effects of marketing actions is necessary. This is when economic coefficients are used above all other means. Economic coefficients include, among others, customer lifetime value and discounted cash flow brand value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 216-222